Daily care for the control of Diabetes mellitus - Simone Cristina Baggio; Sonia Silva Marcon; Aliny de Lima Santos; Catarina Aparecida Sales (Acta Scientiarum. Health Sciences, 2015)
This is a descriptive exploratory qualitative study developed with the purpose of knowing daily cares adopted by diabetic and his/her caregiver for the control of glucose levels. The collection of data was accomplished in 2010, through semi-structured interview, which were later subjected to the content analysis. Eight diabetics and seven family members participated in this study. Our results showed that diabetics find it hard to keep the disease under control and despite the concern of the family with the change of habits they present low adherence to recommended care for metabolic control, especially in relation to food. It is concluded that there is a need to develop strategies aiming the systematization care to people with diabetes involving the sick and the family in the planning of education actions in health, contributing with the development of abilities to a persistent and effective care in the metabolic control according to the reality of each family nucleus.